Efficient Synthesis of 2-Ureaguanines via the in situ Reactions of 2-Isocyanatopurines with Amines - Le Roux, Antoine; Marsault, Eric (Synthesis, 2013)
The synthesis of 2-ureaguanines is reported. The preparation involves a suitably protected intermediate, formation of a 2-isocyanatopurine and in situ trapping with a diverse range of amines followed by double deprotection. This is the first application of 2-isocyanatopurines for the synthesis of 2-ureaguanines.
Keywords: guanine; purines; heterocycles; isocyanates; ureas; triphosgene